A looking-out portal (LOP) approach to enhance qualitative aspects of bandwidth utilisation in academic networks - Ahmed, Waseem; Ansari, Zahid; Herrmann, Johannes U.; Abdullah, Matin Saad (© 2011 Inderscience Enterprises Ltd., 2016)
This article was published in the International Journal of Networking and Virtual Organisations [© 2011 Inderscience Enterprises Ltd.] and the definite version is available at: http://dx.doi.org/10.1504/IJNVO.2011.043802 The Journal's website is at: http://www.inderscience.com/offer.php?id=43802